Clinical impact of probiotics on the efficacy of anti‐PD‐1 monotherapy in patients with nonsmall cell lung cancer: A multicenter retrospective survival analysis study with inverse probability of treatment weighting. Issue 2 (26th March 2021) - Takada, Kazuki; Shimokawa, Mototsugu; Takamori, Shinkichi; Shimamatsu, Shinichiro; Hirai, Fumihiko; Tagawa, Tetsuzo; Okamoto, Tatsuro; Hamatake, Motoharu; Tsuchiya‐Kawano, Yuko; Otsubo, Kohei; Inoue, Koji; Yoneshima, Yasuto; et al.
Abstract: The gastrointestinal microbiota was reported as an important factor for the response to cancer immunotherapy. Probiotics associated with gastrointestinal dysbiosis and bacterial richness may affect the efficacy of cancer immunotherapy drugs. However, the clinical impact of probiotics on the efficacy of cancer immunotherapy in patients with nonsmall cell lung cancer (NSCLC) is poorly understood. The outcomes of 294 patients with advanced or recurrent NSCLC who received antiprogrammed cell death‐1 (PD‐1) therapy (nivolumab or pembrolizumab monotherapy) at three medical centers in Japan were analyzed in our study. We used inverse probability of treatment weighting (IPTW) to minimize the bias arising from the patients' backgrounds. The IPTW‐adjusted Kaplan‐Meier curves showed that progression‐free survival (nonuse vs use: hazard ratio [HR] [95% confidence interval CI] = 1.73 [1.42‐2.11], log‐rank test P = .0229), but not overall survival (nonuse vs use: HR [95%CI] = 1.40 [1.13‐1.74], log‐rank test P = .1835), was significantly longer in patients who received probiotics. Moreover, the IPTW‐adjusted univariate analyses showed that nonuse or use of probiotics was significantly associated with disease control (nonuse vs use: odds ratio [OR] [95%CI] = 0.51 [0.35‐0.74], P = .0004) and overall response (nonuse vs use: OR [95%CI] = 0.43 [0.29‐0.63], P < .0001). In this multicenter and retrospective study, probiotics use was associated with favorable clinical outcomes in patients with advanced or recurrent NSCLC who received anti‐PD‐1 monotherapy. The findings should be validated in a future prospective study. Abstract : What's new? Probiotics associated with gastrointestinal dysbiosis and bacterial richness may affect the efficacy of cancer immunotherapy drugs. However, the clinical impact of probiotics on the efficacy of cancer immunotherapy in patients with nonsmall cell lung cancer (NSCLC) is poorly understood. In this multicenter and retrospective study, probiotics use was associated with favorable clinical outcomes in patients with advanced or recurrent NSCLC who received anti‐PD‐1 monotherapy. Probiotics are a widely‐used drug in the clinical setting with few side effects. The results suggest that prescription of probiotics could be considered in patients with NSCLC who expect to receive immune checkpoint inhibitors.